Mitochondria in the Aging Muscles of Flies and Mice: New Perspectives for Old Characters. (18th August 2016) - Campo, Andrea del; Jaimovich, Enrique; Tevy, Maria Florencia
Abstract : Sarcopenia is the loss of muscle mass accompanied by a decrease in muscle strength and resistance and is the main cause of disability among the elderly. Muscle loss begins long before there is any clear physical impact in the senior adult. Despite all this, the molecular mechanisms underlying muscle aging are far from being understood. Recent studies have identified that not only mitochondrial metabolic dysfunction but also mitochondrial dynamics and mitochondrial calcium uptake could be involved in the degeneration of skeletal muscle mass. Mitochondrial homeostasis influences muscle quality which, in turn, could play a triggering role in signaling of systemic aging. Thus, it has become apparent that mitochondrial status in muscle cells could be a driver of whole body physiology and organismal aging. In the present review, we discuss the existing evidence for the mitochondria related mechanisms underlying the appearance of muscle aging and sarcopenia in flies and mice.